What can metaphor tasks offer for exploring preservice mathematics teachers’ beliefs? - Çiğdem Haser (Netherlands, 2025)
The purpose of this study was to investigate preservice middle school mathematics teachers’ (PMT) beliefs about the nature of mathematics in metaphor tasks when they are designed and analyzed in different ways and their beliefs about mathematics teacher. Nine PMTs attending the practice teaching course completed four metaphor tasks (two open-ended, two structured) about mathematics, mathematics teacher, mathematics teaching and learning through the semester. The metaphors they produced were analyzed both by the revised version (Löfström et al., 2010) of the identity framework by Beijard et al. (2000) and with an inductive analysis. Findings suggested that employing open-ended task structure and inductive analysis might provide more information about PMTs’ beliefs about the nature of mathematics even in metaphors that are not constructed for mathematics.
Proceedings of the Eleventh Congress of the European Society for Research in Mathematics Education